Tricholoma matsutake-derived peptide WFNNAGP protects against DSS-induced colitis by ameliorating oxidative stress and intestinal barrier dysfunction. Issue 23 (5th November 2021) - Li, Mengqi; Lv, Renzhi; Wang, Chuanzhi; Ge, Qi; Du, Hanting; Lin, Songyi
Abstract : WFNNAGP may reduce colonic inflammation in mice by enhancing oxidative defense systems and barrier function and may be a promising candidate for IBD intervention. Abstract : Inflammatory bowel disease (IBD) is a non-specific, chronic inflammatory disease of the intestine. The precise etiology and mechanism underlying the pathogenesis of IBD have not been elucidated. In this study, we investigated the mechanisms through which the Tricholoma matsutake -derived peptide, WFNNAGP, exerts protective effects on the inflammatory response and oxidative stress in a dextran sodium sulfate (DSS)-induced IBD mouse model. WFNNAGP significantly attenuated colitis symptoms in mice, including weight loss, diarrhea, shortened colon, bloody stools, and histopathological changes. WFNNAGP significantly ameliorated the DSS-induced oxidative damage, showing scavenging activity against hydroxyl and DPPH radicals (23.67 ± 4.11% and 34.53 ± 2.45%), increased SOD activity (191.48 ± 4.35 U per mg prot), and decreased MDA activity (1.61 ± 0.24 nmol per mg prot). In addition, WFNNAGP improved the inflammatory response by inhibiting MPO and pro-inflammatory cytokine expression and protected the barrier function by promoting the expression of occludin and ZO-1 in the colon. Western blotting showed that WFNNAGP reduced the inflammatory response by downregulating NF-κB expression and inhibiting the formation and activation of NLRP3 and caspase-1. Thus, WFNNAGP may reduce colonic inflammation in mice by enhancing oxidative defense systems and barrier function and may be a promising candidate for IBD intervention.